Analisis Bibliometrik pada Database Dimensions dengan Kata Kunci “Psikologi Agama” - Aisyah Safitri; Busro Busro (Gunung Djati Conference Series, 2023)
Research related to the Psychology of Religion has been researched by many experts and continues to be developed and published in a variety of scientific contexts. This research attempts to overcome the lack of previous literature studies by emphasizing the comprehensive mapping of the advancement of religion psychology research. This study is a bibliometric analysis on the Dimensions database using a quantitative method to identify research trends in the Psychology of Religion theme. There are five stages carried out in this study, namely determining keywords, data search, article selection, data validation, and data analysis. This research is the result of an analytical view of data related to the discussion of the Psychology of Religion. According to the findings of this study, the study of the Psychology of Religion has attracted the attention of experts. Leading sources or media publications such as Advances in Social Science, Education and Humanities Research are one of the most dominant media in conducting research on the Psychology of Religion. This article contributes to being a reference for future researchers in determining the position of the contribution to the development of more relevant research in the future.